PENINGKATAN KEMAMPUAN SOLFEGIO SISWA MELALUI KEGIATAN EKSTRAKURIKULER PADUAN SUARA DI SMP NEGERI 1 SUNGAI KAKAP - Sari, Elisa Tresna; Mering, Aloysius; Muniir, Asfar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe background of this research is the researcher's awareness to improve the students' solfeggio ability at SMP Negeri 1 Sungai Kakap in a choir.The school choir of SMP Negeri 1 Sungai Kakap is always enthusiastic at participating in some events of Kuburaya district. The problem of this research is how the planning and the implementation which is done can improve the solfeggio ability. The purpose of this research is to improve the students' solfeggio ability through the choir extracurricular activity.The research method that is used in this research was classroom action research in the form of qualitative research. The assessment technique that is used was obtained through performance assessment.The indicator achievement was if there are more than sixteen (16) students got B (51-75) in the third cycle.The research result showed that the student's solfeggio ability at SMP Negeri 1 Sungai Kakap was improving through the choir extracurricular activity. The planning and the implementation was applied by assessing the result from the previous cycles.Â Keywords: ability, solfeggio, extracurricular, choir